Local identification of nonparametric and semiparametric models - Xiaohong Chen; Victor Chernozhukov; Sokbae Lee; Whitney K. Newey (Centre for Microdata Methods and Practice (cemmap), 2011)
In parametric models a sufficient condition for local identification is that the vector of moment conditions is differentiable at the true parameter with full rank derivative matrix. We show that there are corresponding sufficient conditions for nonparametric models. A nonparametric rank condition and differentiability of the moment conditions with respect to a certain norm imply local identification. It turns out these conditions are slightly stronger than needed and are hard to check, so we provide weaker and more primitive conditions. We extend the results to semiparametric models. We illustrate the sufficient conditions with endogenous quantile and single index examples. We also consider a semiparametric habit-based, consumption capital asset pricing model. There we find the rank condition is implied by an integral equation of the second kind having a one-dimensional null space.
Keywords: C12; C13; C23; 330; Identification; Local Identification; Nonparametric Models; Asset Pricing; Finanzmarkt; Capital Asset Pricing Model